Zonisamide upregulates neuregulin-1 expression and enhances acetylcholine receptor clustering at the in vitro neuromuscular junction. (1st September 2021) - Inoue, Taro; Ohkawara, Bisei; Bushra, Samira; Kanbara, Shunsuke; Nakashima, Hiroaki; Koshimizu, Hiroyuki; Tomita, Hiroyuki; Ito, Mikako; Masuda, Akio; Ishiguro, Naoki; Imagama, Shiro; Ohno, Kinji
Abstract: Decreased acetylcholine receptor (AChR) clustering compromises signal transmission at the neuromuscular junction (NMJ) in myasthenia gravis, congenital myasthenic syndromes, and motor neuron diseases. Although the enhancement of AChR clustering at the NMJ is a promising therapeutic strategy for these maladies, no drug is currently available for this enhancement. We previously reported that zonisamide (ZNS), an anti-epileptic and anti-Parkinson's disease drug, enhances neurite elongation of the primary spinal motor neurons (SMNs). As nerve sprouting occurs to compensate for the loss of AChR clusters in human diseases, we examined the effects of ZNS on AChR clustering at the NMJ. To this end, we established a simple and quick co-culture system to reproducibly make in vitro NMJs using C2C12 myotubes and NSC34 motor neurons. ZNS at 1–20 μM enhanced the formation of AChR clusters dose-dependently in co-cultured C2C12 myotubes but not in agrin-treated single cultured C2C12 myotubes. We observed that molecules that conferred responsiveness to ZNS were not secreted into the co-culture medium. We found that 10 μM ZNS upregulated the expression of neuregulin-1 ( Nrg1 ) in co-cultured cells but not in single cultured C2C12 myotubes or single cultured NSC34 motor neurons. In accordance with this observation, inhibition of the Nrg1/ErbB signaling pathways nullified the effect of 10 μM ZNS on the enhancement of AChR clustering in in vitro NMJs. Although agrin was not induced by 10 μM ZNS in co-cultured cells, anti-agrin antibody attenuated ZNS-mediated enhancement of AChR clustering. We conclude that ZNS enhances agrin-dependent AChR-clustering by upregulating the Nrg1/ErbB signaling pathways in the presence of NMJs. Highlights: We made in vitro neuromuscular junctions (NMJs) using cultured cell lines. Zonisamide enhanced acetylcholine receptor (AChR) clustering at the in vitro NMJs. Zonisamide induced no AChR clustering in single cultured agrin-treated myotubes. Zonisamide induced no Nrg1 expression in single cultured neuronal cells. Zonisamide upregulated Nrg1 expression at in vitro NMJs to induce AChR clustering.